Dogfight - Daring, Mason (<<The>> Criterion Collection, 2024)
"An ineffably bittersweet portrait of youth in the 1960s, Nancy Savoca’s funny, sensitive tale of love and war etches two vividly alive characters: aspiring San Francisco folk singer Rose (Lili Taylor) and hotheaded, Vietnam-bound marine Eddie Birdlace (River Phoenix), who meet on the occasion of a cruelly misogynistic party where men compete to bring the most unattractive dates they can find. But what begins as a night to forget unexpectedly develops into something far more meaningful. Featuring music by folk legends Joan Baez, Bob Dylan, and Pete Seeger, Dogfight captures the miracle of human connection while gracefully subverting ideas surrounding machismo, patriotic duty, and the very meaning of America itself." [criterion.com]
Original: USA 1991
Director-approved Blu-ray special edition features: new 2K digital restoration, supervised by director Nancy Savoca, with 2.0 surround DTS-HD Master Audio soundtrack ; audio commentary featuring Savoca and producer Richard Guay ; new interview with Savoca and actor Lili Taylor conducted by filmmaker Mary Harron ; new interviews with cinematographer Bobby Bukowski, production designer Lester W. Cohen, script supervisor Mary Cybulski, music supervisor Jeffrey Kimball, supervising sound editor Tim Squyres, and editor John Tintori ; trailer ; English subtitles for the deaf and hard of hearing ; plus: An essay by film critic Christina Newland
Bildformat 1.85:1
Keywords: Film; Blu-Ray-Disc